The development of didactic and contemplative based teaching materials for human anatomy and physiology - Marneli, Diyyan; Delfita, R; Pratama, M R (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2022)
Existing Human Physiology Anatomy teaching materials tend to have a gap between the content of teaching materials and students, and there is no link to the verses of the Qur'an and the values of Asma al Husna. This study aims to develop didactic and contemplative-based teaching materials for human anatomy and physiology. Research development (R & D) used the ADDIE model. The participants in this study were three experts and 58 sixth semester biology students, majoring in biology department, Tarbiyah and Teachers Training Faculty, IAIN Batusangkar. The research instruments were observation sheets, interview sheets and validation questionnaires. The mean and standard deviation were calculated to determine the validity. Didactic and contemplative teaching materials in the Human Physiology Anatomy course were developed to fulfill all aspects of a development research, according to the characteristics of a teaching material, having didactic and contemplative characteristics. The didactic and contemplative teaching materials developed contain didactic aspects in the form of various activities, according to student learning styles, there is contemplation practice, contains Asma al Husna and contains verses of the Qur'an. The didactic and contemplative teaching materials developed have validity with very valid criteria (3.45Â±0.43). Thus, these teaching materials are suitable for use in classroom learning, fill the gap between the content of teaching materials and students, stop the separation between "knowledge" and "student-self" and deserve to be used as a reference in developing teaching materials that integrate science and religion